Pathological complete response to neoadjuvant trastuzumab and pertuzumab therapy is related to human epidermal growth factor receptor 2 (HER2) amplification level in HER2-amplified breast cancer. Issue 46 (13th November 2020) - Choi, Jin Hyuk; Jeon, Chang Wan; Kim, Young Ok; Jung, Sungui
Abstract : Abstract: The human epidermal growth factor receptor 2 ( HER2 ) is amplified in approximately 20% of breast cancers, and HER2 receptor targeting therapy is associated with a significant improvement in disease-free and overall survival. In several clinical trials, the pathologic complete response (pCR) rate was significantly increased with combined pertuzumab and trastuzumab treatment in HER2 -amplified breast cancer. Although the efficacy and safety of anti- HER2 dual blockade therapy has been reported, the markers that predict the response are still unclear. This study aimed to investigate the relationship between the level of HER2 amplification and the pCR in trastuzumab and pertuzumab neoadjuvant therapy. Twenty-two HER2 -amplified early breast cancer patients who had received neoadjuvant docetaxel, carboplatin, trastuzumab, and pertuzumab (TCHP) therapy were included in this study. HER2 / CEP17 ratio and average HER2 copy number were measured by fluorescence in situ hybridization analysis. The relationship between level of HER2 amplification and tumor pCR status was investigated. The median age was 47.5 years (range, 36–62). 31.8% of the patients were hormone receptor (HR) positive and 68.2%% of the patients were HR negative. The pCR (ypN0/is ypN0) rate in the breast and axilla was 68.2%. The patients who experienced a pCR had a median HER2 / CEP17 ratio of 7.08 (range, 3.16–10.40) and average HER2 copy number of 17.00 (range, 5.85–37.50). The patients who did not experience a pCR had a median ratio of 4.70 (range, 1.06–9.00) and median HER2 copy number of 12.00 (range, 5.85–20.95) ( P  = .030, P  = .174), respectively. pCR was highly correlated with HER2 / CEP17 ratio in neoadjuvant anti- HER2 dual blockade. This suggests that the HER2 / CEP17 ratio can be used as a predictive marker for pCR in neoadjuvant trastuzumab and pertuzumab therapy.